Knowledge, Attitude, Practices, and Sources of Information (KAPS) Toward COVID-19 During the Second Wave Pandemic Among University Population in Qatar: A Cross-Sectional Study - Alkaabi, Ibrahim; Abita, Magdy; Mahdi, Yousif; Ouda, Amr; Malki, Mohammed Imad (Frontiers in Public Health, 2022)
Background: World Health Organization declared COVID-19 as a pandemic on March 11, 2020. Many efforts were performed to contain the virus worldwide. People's Knowledge and attitude should be directed towards strict preventive practices to halt the spread of the virus. We aimed to assess the Knowledge, attitude, practices, and sources of information used by Qatar university attendees. Methods: A cross-sectional web-based questionnaire was administered to 500 employers and students in the Qatar University community. It included questions on Knowledge, Adherence to laws, Practices, and sources of information (KAPS) towards COVID-19. Information on sociodemographic was collected and analyzed. Results: A total of 475 participants aged between 18 and 68 years old consented to complete the survey questionnaire. The study involved 279 (58.7%) non-Qatari nationals, and 196 (41.3%) natives. with 254 (53.5%) participants pursuing postgraduate studies and 221 (46.5%) undergraduates. Around two-thirds of the sample were employed (64.8%), while a third were unemployed (35.2%). Knowledge scores on average were 66.4% (M = 5.31, SD = 1.45, range: 0-8), with only significant differences noted between nationalities (natives and non-natives) Participants average score in practices was 69.72% (M = 4.18, SD = 1.7, range 0-6) with a significant difference in safe COVID-19 practice scores based on educational level. Adherence with COVID-19 policies and rules were 82% (M = 2.46, SD = 0.7, range: 0-3) with no differences noted between groups. The population also reported relying on governmental press conferences (76.0%) as their primary source of gaining details concerning COVID-19, followed by social media (64.4%). The least popular resources were information gained from family, relatives, friends, and coworkers (47.4%) and the news channels on TV (46.7%). Conclusion: Overall, this study provides insights into Qatar's KAPS towards COVID-19 during the quarantine of the second wave of this pandemic. Being the first of its kind to be conducted in the state of Qatar, this study is expected to help the ministry of public health and the government communication office to establish a suitable measurement of response to the spread of COVID-19 and develop the best practices for any future epidemics that might occur.